Assessing Principles of Good Governance: The Case of Lake Wausau, Wisconsin. (2nd September 2019) - Floress, Kristin; Thompson, Aaron; Fisher, Cherie LeBlanc
Abstract: This paper describes how in‐depth interviews and content analysis of water‐related policies and plans were used to assess good governance principles (transparency, effectiveness, equity, accountability, and appropriate scale) for Lake Wausau in central Wisconsin. The purpose of the research was to support and inform development of a lake management plan. One of the key findings was that the existing system of water governance lacked transparency. In addition, responsibility for and benefits from potential improved lake conditions were distributed unevenly and inequitably among stakeholders. Local and county plans were vague and lacked strong language (e.g., "should" vs. "must" comply) to indicate which actions were required. Both barriers to and opportunities for creating a more effective system were identified. This paper offers suggestions for improving the governance system, discusses the limits of local watershed planning for overcoming watershed management issues, and provides suggestions for anyone wishing to undertake governance analyses to support water resources management.